2004
DOI: 10.1074/jbc.m408806200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Stabilization by Osmolytes from Hyperthermophiles

Abstract: 2-O-␣-Mannosylglycerate, a negatively charged osmolyte widely distributed among (hyper)thermophilic microorganisms, is known to provide notable protection to proteins against thermal denaturation. To study the mechanism responsible for protein stabilization, picosecond time-resolved fluorescence spectroscopy was used to characterize the thermal unfolding of a model protein, Staphylococcus aureus recombinant nuclease A (SNase), in the presence or absence of mannosylglycerate. The fluorescence decay times are si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 53 publications
(45 reference statements)
2
15
0
Order By: Relevance
“…In addition, IF confirms a higher stability of rLAP fd up to 85 • C when a red displacement of max was observed (Fig. 3B) which is consistent with previous IF responses in other protein studies [46][47][48]. For rLAP uf IF revealed that the folding process occurs below 40 • C, based on the blue shift of max , whereas the thermal denaturation takes place from 40 • C until 60 • C. Unlike to IF, DSC has a lower sensitivity to detect gradual molecular transitions of subtle exothermic enthalpies during the establishment of hydrogen bonds; however, it is capable to detect the single endothermic transition that comprises the rupture of all the non-covalent interactions.…”
Section: Increased Thermal Stability Of Rlapsupporting
confidence: 93%
“…In addition, IF confirms a higher stability of rLAP fd up to 85 • C when a red displacement of max was observed (Fig. 3B) which is consistent with previous IF responses in other protein studies [46][47][48]. For rLAP uf IF revealed that the folding process occurs below 40 • C, based on the blue shift of max , whereas the thermal denaturation takes place from 40 • C until 60 • C. Unlike to IF, DSC has a lower sensitivity to detect gradual molecular transitions of subtle exothermic enthalpies during the establishment of hydrogen bonds; however, it is capable to detect the single endothermic transition that comprises the rupture of all the non-covalent interactions.…”
Section: Increased Thermal Stability Of Rlapsupporting
confidence: 93%
“…It should be noted that introduction of osmolytes into solution under conditions of their exclusion from the immediate vicinity of the protein increases the chemical potential of the systems, i.e., it destabilizes it [25][26][27][28]. Stabilization of proteins in solutions in the presence of osmolytes is due to the fact that the concentration of osmolyte molecules in the immediate vicinity of unfolded protein is lower than in the vicinity of a native protein [39,40]. Correspondingly, the difference in chemical potentials between the native and denatured protein states in solution in the presence of osmolytes is higher than in buffer solutions.…”
Section: Osmolytes Of Class II Increase (mentioning
confidence: 99%
“…When the Trp side chain in the free target peptide is surrounded by water molecules, the fluorescence spectra are characterized by an emission centered near 355 nm. However, if the Trp residue becomes buried in a hydrophobic region when the peptide binds to CaM, the fluorescence emission undergoes a blue shift and typically an increase in the fluorescence intensity (32,33).…”
Section: Fluorescence Spectroscopy Reveals a Different Stoichiometry mentioning
confidence: 99%